The EQ-5D and EQ-HWB fit the perceptions of quality of life from a Chinese perspective: a concept mapping study - Yifan Ding; Zhuxin Mao; Zhihao Yang; Siliu Feng; Jan Busschbach (Health and Quality of Life Outcomes)
Abstract Background The escalating globalization of health assessments underscores a pivotal challenge: Do Quality of Life (QoL) instruments, developed primarily in Western contexts, accurately reflect the perspectives of non-Western populations? This study evaluates the alignment of EQ-5D and EQ-HWB items with QoL dimensions identified in Chinese literature, and compares QoL perceptions between Chinese residents and those living abroad who may be influenced by Western values. Methods This study employed three successive rounds of participant recruitment to refine the concept mapping process. Initially, 13 bilingual QoL experts in the Netherlands piloted the methodology, providing feedback on item translation and expression. Subsequently, 18 Chinese expatriates in the Netherlands, with partial education abroad, reviewed the revised materials to represent perspectives influenced by Western culture. Finally, 20 native Chinese residents, who were born and educated in China, formed the target group. Utilizing feedback from the pilot stage, a pool of 54 QoL items derived from Chinese literature, plus an additional eight from the EQ-HWB, were assembled. The Group Concept Mapping (GCM) method was used, with participants organizing the items to reflect their interrelationships. Data were analyzed via Groupwisdom™, an online tool supporting multidimensional scaling (MDS) and cluster analysis, culminating in visual cluster rating maps that highlighted the item associations and groupings. Results In China, a five-cluster MDS map was identified: personal abilities, family and society, physical health, mental health, and self-cognition (stress value: 0.183), with physical health prioritized. Abroad, four clusters appeared: mental health, social connections, daily activities, and physical function (stress value: 0.185), prioritizing social connections. The EQ-5D missed the "family and society" cluster in China and "social connections" abroad. In contrast, the EQ-HWB covered all clusters in both groups. Conclusions The EQ-5D items align well with the somatic and partially with the mental clusters, while the EQ-HWB also covers the adaptation cluster and the remaining mental cluster aspects. Both instruments reflect the QoL perceptions of Chinese individuals, although EQ-5D focuses more on health than overall well-being. Cultural differences affect priorities: participants in China value physical health most, whereas those abroad emphasize social connections.